Implementation of the concept of tax expenditures in the Russian Federation: the evaluation methodology of effects and efficiency - Mayburov, I.A.; Leontyeva, Y.V. (Економіка промисловості, 2014)
The subject actualized in the article is the need to develop an evaluation methodology of the tax expenditures efficiency as well as tax incentives efficiency for the purpose of tax accounting and optimization. The basic structure of taxes and the normative structure of taxes are distinguished in the article. The basic structure of taxes did not originally contain any advantages for certain activities or groups of taxpayers, representing some ideal theoretical tax construction. As a normative structure of Russian income authors consider taxation in various degrees (different rates applied) of different types of income, and the taxation of one part of the total income according to the model Schantz-Haig-Simons. The authors propose an algorithm for tax expenditures estimating. A method of tax expenditures estimation according to the analyzed tax incentive for the estimated period is proposed. The initial requirements for assessing the tax incentives efficiency are formulated. It is proposed to distinguish between four types of effects (fiscal, social, economic, budget, and ecological) and the same types of efficiency.The ways to calculate these types of efficiency are suggested. Fiscal efficiency of tax incentive is the ratio of the fiscal effect of the provision of incentives received in the period t, when a real effect from the action of the incentives appears to the tax expenditures in the same period t. Social efficiency of the tax incentive is the ratio of the social impact of the provi- sion of incentives received in the period t, when the real effect of the action of this incentive appears to the amount of tax expenditures over the same period. The economic efficiency of the tax incentives is the ratio the economic effect from the provision of incen-tives received in the period t, when the real effect of the action of this incentive appears to the sum of tax expenditures of the same period t. The need for using the budget efficiency of the tax incentives as an integral index is proved. Budgetary effect of tax incentives may be represented as the sum of the fiscal, social and economic effects